Late Transition Metal-Carboryne Complexes Synthesis, Structure, Bonding, and Reaction with Alkenes and Alkynes - Qiu, Zaozao (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2012)
In this thesis, Zaozao Qiu shows that transition metals can mediate or catalyze cycloaddition and coupling reactions of carboryne with alkynes or alkenes. These reactions afford benzocarboranes, alkenylcarboranes or dihydrobenzocarboranes, and are powerful strategies to assemble useful complex molecules in a single operation from very simple precursors. Carboranes have many applications in medicine. However, their unique structures make derivatization difficult and until now limited efficient synthetic methods to obtain functional carborane materials have restricted their application. This work breaks new ground in metal-carboryne chemistry and will have a significant impact on synthetic, cluster and materials chemistry.  .